Evaluation of the fully automated BD MAX Cdiff and Xpert C. difficile assays for direct detection of Clostridium difficile in stool specimens - Dalpke, Alexander; Hofko, Marjeta; Zorn, Markus; Zimmermann, Stefan (Journal of clinical microbiology, 2013)
We evaluated the fully automated molecular BD MAX Cdiff assay (BD Diagnostics) and the Xpert C. difficile test (Cepheid) for rapid detection of Clostridium difficile infection. Culture was done on chromogenic agar followed by matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry identification and toxin detection. Repeat testing was required for 1.8% and 6.0% of the BD MAX and Xpert tests, respectively. Sensitivities, specificities, positive predictive values (PPV), and negative predictive values (NPV) were 90.5%, 97.9%, 89.3%, and 98.1%, respectively, for BD MAX and 97.3%, 97.9%, 90.0%, and 99.5%, respectively, for Xpert.